American Orthopaedic Association's (AOA) Council of Orthopaedic Residency Directors (CORD) 2019 Summer Conference: Top Abstracts*. (3rd March 2021) - Weistroffer, Joseph K.; Patt, Joshua C.
Abstract : In a continuing collaboration between the American Orthopaedic Association's (AOA) Council of Orthopaedic Residency Directors (CORD) and JBJS, the following 10 abstracts highlight the scientific research presented at AOA's annual national meeting that was held in June 2019 in San Diego, California. These abstracts embody CORD's purpose and mission: "The American Orthopaedic Association's Council of Orthopaedic Residency Directors (CORD) program strives to recognize best practices in orthopaedic residency education and fellowship education based on ACGME [Accreditation Council for Graduate Medical Education]-defined essential knowledge and skills in each of the residency education competency areas. CORD provides a forum for academic orthopaedic leaders to exchange ideas, discuss solutions to challenges, and find ways to teach residents in orthopaedic programs effectively." We hope that this education-related research will inspire further inquiry to advance the development of future orthopaedic surgeons.